Mastering Prezi for business presentations : engage your audience visually with stunning Prezi presentation designs and be the envy of your colleagues who use PowerPoint /: engage your audience visually with stunning Prezi presentation designs and be the envy of your colleagues who use PowerPoint. (2012) - Anderson-Williams, Russell
No abstract available